Pengaruh Penggunaan Media Pembelajaran Audio Visual Berbasis Quizizz terhadap Minat Belajar Siswa pada Mata Pelajaran Pendidikan Agama Kristen Kelas XI di SMA Negeri 1 Tukka Kecamatan Pandan Kabupaten Tapanuli Tengah Tahun Pembelajaran 2023/2024 - Kristina Mendrofa; Eben H. Telaumbanua; Sabar Rudi Sitompul; Maria Widiastuti; Lasmaria Lumban Tobing (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The research aims to determine the positive and significant influence of using quizizz-based audio-visual learning media on students' interest in learning in class XI Christian Religious Education subjects at SMA Negeri 1 Tukka, Central Tapanuli Regency for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the use of quizizz-based audio visual learning media on students' interest in learning in class XI Christian Religious Education subjects at SMA Negeri 1 Tukka, Central Tapanuli Regency for the 2023/2024 academic year. The One-Group Pre-Post Design research method is an experiment carried out on just one group without a comparison group. The population of all class The sample was purposive sampling, namely students of class XI IPA 1 and XI IPA 2 with a total of 44 people. The research instrument is a closed questionnaire. The results of data analysis obtained: a) The value rcount=0.603>rtabel=0.297 and tcount=4.899>ttable=2.021 shows that there is a positive and significant relationship between the use of quizizz-based audio visual learning media and students' interest in learning in Christian Religious Education subjects. b) Regression equation. c) The determination test revealed that the magnitude of the effect was 36.39%. d) Hypothesis testing obtained Fcount=23.914>Ftable=3.23, so H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the use of quizizz-based audio visual learning media on students' interest in learning in class XI Christian Religious Education subjects at SMA Negeri 1 Tukka, Central Tapanuli Regency for the 2023/2024 academic year.